Evaluation of Instruments on Online Self-Directed Learning Methods in Secondary Schools Using the Rasch Model - Nurhidayat, Arif (Sean Institute, 2025)
Online learning requires students to possess strong self-directed learning abilities to ensure that the learning process remains effective. To ensure the accurate measurement of these abilities, an evaluation instrument with sound measurement quality is essential. This study aims to analyze the validity and reliability of the Self-Directed Online Learning instrument among secondary school students using the Rasch Model. The study employed a descriptive quantitative approach involving 757 secondary school students as respondents. The research instrument was the Self-Directed Online Learning Scale (SDOLS), consisting of 17 items measured on a five-point Likert scale. Data analysis was conducted using the Rasch Model with the assistance of Winsteps software. The results indicate that 15 items met the validity criteria based on the Outfit Mean Square (MNSQ) values, while 2 items did not meet the required criteria. Reliability analysis shows that the instrument demonstrates adequate reliability, while respondent reliability falls into the good category. These findings suggest that the Self-Directed Online Learning instrument is appropriate for measuring students’ self-directed learning in online learning at the secondary school level, although refinement of several items that do not meet the criteria is recommended.